2013
DOI: 10.1038/sc.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidepressant and treadmill gait training on recovery from spinal cord injury in rats

Abstract: Study design: Experimental, controlled, animal study. Objectives: To evaluate the influences of antidepressant treatment, treadmill gait training and a combination of these therapies in rats with experimental, acute spinal cord injury (SCI). Setting: Brazil. Methods: 48 Wistar rats were given standardized SCI; rats were then randomly assigned to four treatment groups: (1) motor rehabilitation therapy for 1 hour daily (gait training); (2) daily treatment with the antidepressant, fluoxetine (0.3 ml per 100 g int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…In the present study, we found a significant increase in BDNF expression in rat motoneurons innervating the tibialis anterior and soleus muscles after SCI and long-term treadmill-training as compared to the untrained rats. BDNF is a well-studied neurotrophin, expressed in motoneurons of the CNS, and has been shown to promote protection, and axonal and dendritic growth through localized or paracrine effects (Carty et al, 2013;Cortes et al, 2013;Cristante et al, 2013;O'Donnell and Harvey, 2013;Terson de Paleville et al, 2013). Given that BDNF can act locally on the motoneuron soma as well as through dendritic transport (Rind et al, 2005), such upregulation could potentiate both protective and dendritic growth effects in the motoneuron pools of these hindlimb muscles.…”
Section: Treadmill Training Increased Expression Of Bdnf In Lumbar Momentioning
confidence: 95%
“…In the present study, we found a significant increase in BDNF expression in rat motoneurons innervating the tibialis anterior and soleus muscles after SCI and long-term treadmill-training as compared to the untrained rats. BDNF is a well-studied neurotrophin, expressed in motoneurons of the CNS, and has been shown to promote protection, and axonal and dendritic growth through localized or paracrine effects (Carty et al, 2013;Cortes et al, 2013;Cristante et al, 2013;O'Donnell and Harvey, 2013;Terson de Paleville et al, 2013). Given that BDNF can act locally on the motoneuron soma as well as through dendritic transport (Rind et al, 2005), such upregulation could potentiate both protective and dendritic growth effects in the motoneuron pools of these hindlimb muscles.…”
Section: Treadmill Training Increased Expression Of Bdnf In Lumbar Momentioning
confidence: 95%
“…Intraperitoneal injection of fluoxetine combined with exercise training significantly increased BDNF in the hippocampus which promoted nerve regeneration and BBB score [73, 74]. The combined use of meta-chlorophenylpiperazine (mCPP) and quipazine in SCI not only improved BBB scores but also improved weight-bearing walking [66].…”
Section: The Effect Of Combinatorial Strategy With Exercisementioning
confidence: 99%
“…Indeed, other studies suggest that this antidepressant may have beneficial effects on recovery of function. For example, studies have shown that fluoxetine treatment improves locomotor function after an incomplete SCI, [30][31][32] and others have found that increasing serotonergic activity is associated with improvements in motor movement. [33][34][35][36] Because the focus of the present study was on the reversal of depression, we used a dose of fluoxetine that has been shown to be subthreshold for increasing motor activity per se (5 mg/kg/day), 36 which may confound the interpretation of depression-like behavior for motor-dependent tasks (e.g., open-field activity), and extended previous analyses looking at the effects of fluoxetine on sensory, as well as locomotor, recovery after SCI.…”
Section: Introductionmentioning
confidence: 99%